Spring durum wheat yield capacity in the Left-Bank Forest-Steppe - Liashenko, V.; Polezhak, Ye. (Scientific Progress & Innovations, 2024)
Spring durum wheat is a valuable food crop, from which high-quality flour is received for manufacturing macaroni products and grits having high nutritive value. Modern varieties of spring durum wheat can provide yields of 4.5–5.0 t/ha, in contrast to the varieties of winter durum wheat as the former ones are characterized by a considerable plasticity and stability to the environmental conditions as well as a short growing period. This allows introduce the crop into the structure of rotation systems in all zones of Ukraine and use it as an assurance crop for reseeding perished sown areas of winter wheat. The article deals with the increase in the volumes of growing spring durum wheat in Ukraine, which is stipulated by the corresponding conditions, including large areas under sowing and favorable climate. Owing to these factors, both the domestic market will be provided with high-quality raw materials for manufacturing products and the international market in the EU countries, which import grain from Canada, the USA, and Turkey. The experiments were conducted during 2022–2024 in Hlobyne district of Poltava region. Two varieties of spring durum wheat were used in the research: of Ukrainian selection (Nashchadok, of V. Ya. Yurieva Institute of Plant Growing of the National Academy of Agrarian Sciences), and of foreign selection (Acvilon, KVS Lokhov GmbX, Germany). It has been determined that the variety of spring durum wheat of Ukrainian selection has the best yield indicators under unstable weather and climatic conditions – at the level of 4.2–4.5 t/ha. It was calculated that in the most favorable year of 2023 the yield of Acvilon variety was by 18.4 % lower than that of Nashchadok variety, and in 2022 and 2024 – by 22.9 % and 35.5 %, respectively. Moreover, the unfavorable weather conditions of 2024 resulted in the yield decrease of Nashchadok variety by 6.7 % and of Acvilon variety – by 18.4 %. It has been substantiated that under the conditions of the Left-Bank Forest-Steppe of Ukraine, it is expedient to cultivate the regionalized Nashchadok variety fertilized with Macrostar NPK 8:15:15 (100 kg/ha) during the sowing period and with Naturamin WPS (0.2 kg/ha) fertilization in the layering phase.